Interleukin–33, Oxidative Stress in Prediabetic Polycystic Ovary Syndrome Patients with Insulin Resistance - Al-Taie, Wafa F.; AL-Rubaei, Zainab M.; Hassan, Abeer Jabbar (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Polycystic ovary syndrome (PCOS) is one of the common female endocrine disorders of uncertain etiology, which causes menstrual disorders as well as infertility. Interleukin–33(IL-33) is considered as a strong risk marker of inflammation and may have possible role in pathogenesis of PCOS. Objectives: The present study is designed to investigate the possible role of IL-33 in pathogenesis of PCOS and its relation with glycated hemoglobin (HbA1C),insulin resistance(IR) and oxidative stress in prediabetic PCOS patients. Subjects and Methods: The study involved 30 healthy women as control group and sixty six infertile Iraqi women with PCOS which were divided into two groups according to glycated heamoglobin(HbA1c) value and homeostasis model assessment for insulin resistance (HOMA-IR). The first group (G1) consist of 30 women with HbA1c ≤ 6.5% and HOMA –IR<3.8 as PCOS without diabetes and without insulin resistance. The second group(G2) consist of 36 patients with HbA1c ≥ 6.5 % and HOMA-IR ≥ 3.8 as PCOS with pre diabetes type 2 and insulin resistance. Ten milliliters of blood were collected from all subjects by vein puncture during 2nd – 4th day of the menstrual cycle. Two ml of blood were collected in EDTA tube for HbA1c analysis. The serum which obtained from the remained blood were used for determination of (insulin, fasting blood glucose(FBG), Malondialdehyde(MDA) , Total antioxidant capacity(TAC) , uric acid, glutathione(GSH), albumin, and IL-33) . Results: Results revealed a significant elevation in HbA1c, insulin, HOMA-IR, MDA, TAC, uric acid and IL-33 in the patients group when compared with healthy women. On the other hand, a significant decreased in GSH and albumin were found in patients group when compared with control group. Also there are significant differences in the results between patients in group 1 and group 2. A significant positive correlation between IL-33 and HbA1c levels was noticed in G1 and G2 .A significant positive correlation between IL-33 and HOMA-IR was noticed in group 1 while a negative significant correlation was found in group 2. No correlation founded between IL-33 levels and TAC concentration in group 1, but a positive correlation noticed with group 2. A significant negative correlation was observed between IL-33 and MDA/TAS ratio in G1, while a significant positive correlation in G2 was found. Conclusion: high levels of IL-33 in patient groups may be considered as a novel cytokine involved in the pathogenesis of PCOS. Also the elevation in oxidative stress in PCOS patients could be a reason for disturbed follicular development and ultimately infertility.